Ketoacidosis admission rate in type 2 diabetes mellitus patients from 2006 to 2015 in Abruzzo, Italy. (13th November 2019) - Meo, F; Di Giovanni, P; Cedrone, F; Di Martino, G; Scampoli, P; Staniscia, T
Abstract: Background: Diabetic ketoacidosis (DKA) is a potentially life-threatening but largely preventable complication of diabetes and is associated with significant health care utilization and expenditure. Whereas DKA is mostly related to type 1 diabetes, over recent years an increasing number of hospital admissions for DKA have been reported in adult subjects with type 2 diabetes. The aim of this study was to assess the trend of hospitalizations for DKA in adult patients with type 2 diabetes and its associated factors. Methods: A retrospective cross-sectional study was performed from 2006 to 2015 in Abruzzo region. Data were collected from hospital discharge records (HDRs) of type 2 diabetes adult patients with either primary or secondary diagnosis for DKA. Age-adjusted hospitalization rates were computed by gender and standardized on the regional population in 2006. A logistic regression model was implemented using the presence of DKA as dependent variable. Results: We identified 160, 366 HDRs with type 2 diabetes. Out of them, 1611 (1.00%) were due to DKA. The hospitalization rates for DKA increased both for male +115.9 and female +142.8%, from 2006 to 2015. Associated factors of DKA were age ranging from 18 to 44 (adjOR=4.17; 95%CI:3.27-4.31), uncontrolled diabetes (adjOR=1.79; 95%CI:1.60-2.01), trauma (adjOR=1.38; 95%CI:1.13-1.68), any infection (adjOR=1.68; 95%CI:1.22-.2.33), liver disease (adjOR=1.29; 95%CI:1.09-1.53), fluid and electrolyte disorders (adjOR=2.09; 95%CI:1.09-1.53), psychosis (adjOR=1.69; 95%CI:1.25-2.30). Conclusions: Hospitalization trends for DKA in adult patients with type 2 diabetes have been increasing and are associated with some comorbidities. Early screening, appropriate patients, families and communities education remain an important aspect of preventing an acute diabetic complication such as DKA. Moreover, multimorbidity complicates the disease management and remains an open challenge for public health. Key messages: This study addresses hospitalizations for DKA in adult patients with type 2 diabetes, an occurrence increasing worldwide for unclear reasons. For preventing DKA in type 2 diabetes patients, it is useful taking into consideration the known trigger factors, but it is also worthwhile improving the management of comorbidities in outpatients.